COMPUTER-ASSISTED LANGUAGE LEARNING IN THE FOREIGN LANGUAGE CLASSROOMS - Cayandrawati Sutiono (Vidya Karya, 2013)
There are many on-line applications of CALL that can be used in the English language learning classrooms. These applications have a lot of advantages despite their barriers. Through the use of CALL, English learners are expected to be able to communicate across languages and cultures. It lets learners of a language communicate inexpensively with other learners or native speakers. Using CALL, teachers are not the only source of information any more, but act as facilitators. Moreover, students become active learners and they are encouraged to be explorers and creators of language rather than passive recipients. Therefore, this paper will review and discuss using internet in the classroom, in particular CALL, the benefits of employing CALL, the barriers that CALL presents in our language classroom, and the guidelines of using internet in the classroom.